Contribution of human immunodeficiency virus type 1 minority variants to reduced drug susceptibility in patients on an integrase strand transfer inhibitor-based therapy - Gibson, Richard M; Weber, Jan; Winner, Dane; Miller, Michael D; Quiñones-Mateu, Miguel E (PloS one, 2014)
The role of HIV-1 minority variants on transmission, pathogenesis, and virologic failure to antiretroviral regimens has been explored; however, most studies of low-level HIV-1 drug-resistant variants have focused in single target regions. Here we used a novel HIV-1 genotypic assay based on deep sequencing, DEEPGEN (Gibson et al 2014 Antimicrob Agents Chemother 58∶2167) to simultaneously analyze the presence of minority variants carrying mutations associated with reduced susceptibility to protease (PR), reverse transcriptase (RT), and integrase strand transfer integrase inhibitors (INSTIs), as well as HIV-1 coreceptor tropism. gag-p2/NCp7/p1/p6/pol-PR/RT/INT and env/C2V3 PCR products were obtained from twelve heavily treatment-experienced patients experiencing virologic failure while participating in a 48-week dose-ranging study of elvitegravir (GS-US-183-0105). Deep sequencing results were compared with (i) virological response to treatment, (ii) genotyping based on population sequencing, (iii) phenotyping data using PhenoSense and VIRALARTS, and (iv) HIV-1 coreceptor tropism based on the phenotypic test VERITROP. Most patients failed the antiretroviral regimen with numerous pre-existing mutations in the PR and RT, and additionally newly acquired INSTI-resistance mutations as determined by population sequencing (mean 9.4, 5.3, and 1.4 PI- RTI-, and INSTI-resistance mutations, respectively). Interestingly, since DEEPGEN allows the accurate detection of amino acid substitutions at frequencies as low as 1% of the population, a series of additional drug resistance mutations were detected by deep sequencing (mean 2.5, 1.5, and 0.9, respectively). The presence of these low-abundance HIV-1 variants was associated with drug susceptibility, replicative fitness, and coreceptor tropism determined using sensitive phenotypic assays, enhancing the overall burden of resistance to all four antiretroviral drug classes. Further longitudinal studies based on deep sequencing tests will help to clarify (i) the potential impact of minority HIV-1 drug resistant variants in response to antiretroviral therapy and (ii) the importance of the detection of HIV minority variants in the clinical practice.
Keywords: Drug Resistance, Multiple; Humans; Anti-HIV Agents; HIV-integrasa; Dose-Response Relationship, Drug; Genotyping Techniques; mutace; HIV Integrase Inhibitors; Viral Tropism; Phenotype; genotypizační techniky; lidé; zvířata; myši; Virus Replication; Mice; mnohočetná léková rezistence; buněčné linie; virová léková rezistence; Cell Line; fenotyp; inhibitory HIV-integrasy; replikace viru; Drug Resistance, Viral; látky proti HIV; vysoce účinné nukleotidové sekvenování; tropismus virů; High-Throughput Nucleotide Sequencing; vztah mezi dávkou a účinkem léčiva; Animals; HIV Integrase; Mutation; HIV-1